Emerging photovoltaic technologies - Jean, Joel; Brown, Patrick Richard (IOP ebooks. 2020 collection., 2020)
Solar photovoltaics (PV) is the fastest-growing energy technology in the world today and an important tool for mitigating climate change. Crystalline silicon PV modules are now affordable, efficient, reliable, and dominant in the global market. So why do researchers and entrepreneurs continue to pursue new PV technologies? This book explores how market forces expose opportunities for new solar technologies. The authors explain how two emerging thin-film PV technologies--metal halide perovskites and colloidal quantum dots--can benefit from rapid scalability, reduced manufacturing and installation costs, and new modes of deployment. This book is targeted at students, early-career researchers, and industry newcomers seeking to maximize their impact in the field of emerging thin-film solar photovoltaics.